She's too pretty to burn (Dreamscape Media, Henry Holt and Company, 2021)
When seventeen-year-old Veronica's photograph of her introverted girlfriend goes viral, they are sent into a spiral of fame and lethal danger as they navigate the turbulent waters of their relationship, secrets, acclaim, and the underground San Diego art scene.